Quality of life in patients with chronic renal failure on hemodialysis: analysis of associated factors - Silva, Guilherme Dallapicola (2016)
OBJECTIVES: To evaluate the quality of life (QOL) and related factors in patients with chronic renal failure submitted to hemodialysis in the municipality of São Mateus/ES.METHODS: A descriptive study, cross-sectional and quantitative approach. Sociodemographic data, clinical and QOL were collected through interviews using a structured questionnaire. For the assessment of QoL used the specific instrument Kidney Disease and Quality of Life-Short Form (KDQOL-SFTM). For analysis, the fields were summarized into three components: component summarized kidney disease (CDRS), physical component summary (PCS) and mental component summary (CMS).RESULTS: We interviewed 168 patients. There was a predominance of men (60.1%), the 60-69 age group (21.4%) and treatment time ≤ 2 years (41.6%). The average global health assessment was 71.31 (± 23.23). They observed significant and independent associations between the components summarized the variables age, gender, evaluation of the trip, comorbidities and transport funded by the municipality.CONCLUSIONS: The QOL of the studied population, in general, is compromised and some factors such as the presence of comorbidities, age and transport to the clinic are determinant.